Legal Protection of Children in the Investigation Process by Investigators Based on Restorative Justice - Askohar Askohar; Siti Rodhiyah Dwi Istinah (Universitas Islam Sultan Agung, 2021)
This study aims to analyze more deeply related to child protection in the current investigation process. The type of approach in this research is sociological juridical. Based on the analysis of the existing data, it was found that the child protection in the investigation process in Central Java has not been able to run effectively, Most of the children or adolescents in Central Java who are in conflict with the law are decided by the judge to enter the juvenile prison. In addition, the lengthy legal process against children in conflict with the law results in the child being depressed and can make the child's psychology more shaken. This will obviously result in the growth and development of the child's soul and also the future of the child. Restorative justice is present as another effort to enforce the law by not injuring children's rights, restorative justice is carried out by diversion. Restorative justice in handling children in conflict with the law can be pursued in law enforcement through diversion efforts. Implementation of diversion in the case of children for children with a criminal sanction of 1 year.